Sclerotioloids A–C: Three New Alkaloids from the Marine-Derived Fungus Aspergillus sclerotiorum ST0501 - Mao, Jun-Qiu; Zheng, Yao-Yao; Wang, Chang-Yun; Liu, Yang; Yao, Guang-Shan (Marine drugs, 2023)
Alkaloids, as one of the largest classes of natural products with diverse structures, are an important source of innovative medicines. Filamentous fungi, especially those derived from the marine environment, are one of the major producers of alkaloids. In this study, three new alkaloids, sclerotioloids A–C (1–3), along with six known analogs (4–9), were obtained under the guidance of the MS/MS-based molecular networking from the marine-derived fungus, Aspergillus sclerotiorum ST0501, collected from the South China Sea. Their chemical structures were elucidated by comprehensive analysis of the spectroscopic data, including 1D and 2D NMR and HRESIMS. Additionally, the configuration of compound 2 was unambiguously determined by X-ray single crystal diffraction, and that of compound 3 was determined by the TDDFT-ECD approach. Sclerotioloid A (1) represents the first example of 2,5-diketopiperazine alkaloid with a rare terminal alkyne. Sclerotioloid B (2) showed the inhibition of NO production induced by lipopolysaccharide (LPS), with an inhibition rate of 28.92% higher than that of dexamethasone (25.87%). These results expanded the library of fungal-derived alkaloids and further prove the potential of marine fungi in the generation of alkaloids with new scaffolds.